Anterior Segment Optical Coherence Tomography Signs of Local Dilatation Effect of a Micro-Stent on Schlemm’s Canal - Gillmann, Kevin; Bravetti, Giorgio Enrico; Mansouri, Kaweh; Mermoud, André (Nepalese Journal of Ophthalmology, 2018)
Introduction: The iStent inject® (Glaukos Corporation, CA, USA) is a relatively new device designed to be implanted ab-interno through the trabecular meshwork. This is, to the best of our knowledge, the first in-vivo description of a trabecular bypass device visualised with anterior segment optical coherence tomography (AS-OCT), and report of its structural effect on Schlemm’s canal.Case Report: A 74 year-old female patient suffering from long-standing primary open-angle glaucoma and nuclear sclerosis underwent cataract surgery combined with the implantation of two iStent injects®. Surgery was uncomplicated and achieved intraocular pressure (-1 mmHg) and medication (-2 molecules) reduction at 6 months. Under AS-OCT (Spectralis OCT, Heidelberg Engineering AG, Germany) the stent appears as a 300 μm long hyper reflective hollow device within the trabecular meshwork. Approximately a third of it protruded into the anterior chamber. Profound OCT signal loss was notable within the shadow of the device. A second AS-OCT section 500 μm beside the microstent shows a markedly dilated Schlemm’s canal, with a major diameter of 390 μm.Discussions: This report confirms that AS-OCT is a suitable technique to assess microstent positioning, and provides a first report on the in-vivo appearance of a functioning stent. It also indicates that iStent injects® could have a tangible effect on adjacent portions of Schlemm’s canal with, in this case, a 220% increase in canal diameter compared to the observed average (122 μm). This suggests the IOP-lowering effect of trabecular bypass devices could rely on a  dual mechanism involving Schlemm’s canal dilatation.